KEUNTUNGANDAN RISIKO USAHA MINI PURSE SEINE DI DESA SATHEAN - Frischilla Pentury; Eygner Gerald Talakua; Tati Ngangun (Universitas Pattimura, 2017)
The low profits of mini purse seine in Sathean Village will have an impact on the business risks being carried out. The new paradigm states that the relationship between risk and profit levels is quadratic; too much risk can lead to the loss and even destruction of a business. Thus, the fisherman of mini purse seine business owners in Sathean Village needs to manage their business risk well to achieve optimum profit for business sustainability. This study aims to assess business profits and business risks. Primary data was collected on 6 fisherman owners of mini purse seine business owners in Sathean Village as respondents, conducted business profit analysis and business risk calculation based on probability density. The results showed that the business profit was Rp 241,608,203/year or Rp 196,551,994 in the peak season, Rp 41.828.721 in the medium season and Rp 3.2227.488 in the less season.In peak and less seasons, these businesses are at risk or have the opportunity to lose, while in the medium season is not risky.